2002
DOI: 10.1002/ijc.10670
|View full text |Cite
|
Sign up to set email alerts
|

After hMSH2 and hMLH1—what next? Analysis of three‐generational, population‐based, early‐onset colorectal cancer families

Abstract: The aim of our study was to examine the role of genetic factors on early-onset colorectal cancer after excluding the impact of germline mutations in the two major mismatch repair genes. A total of 131 incident probands, under 45 years at diagnosis of a first primary colorectal cancer selected from the Victorian Cancer Registry, and their first-and seconddegree relatives, were interviewed. Germline DNA from all 12 probands with a family history meeting the modified Amsterdam Criteria for Hereditary Non-Polyposi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 25 publications
1
35
1
Order By: Relevance
“…This is in agreement with results from computational modeling (Chao, et al, 2008) and clinical observations such as early age of onset and perfect co-segregation of mutation and disease. Also, MSI and the (Chialina, et al, 2006;Jenkins, et al, 2002;Leach, et al, 1993;Southey, et al, 2005). Similar to studies in yeast expressing the equivalent mutant protein, yMSH2-P640L (Drotschmann, et al, 1999;Polaczek, et al, 1998), we observed a strong mutator phenotype in Msh2 P622L/P622L ESCs.…”
Section: Discussionsupporting
confidence: 85%
“…This is in agreement with results from computational modeling (Chao, et al, 2008) and clinical observations such as early age of onset and perfect co-segregation of mutation and disease. Also, MSI and the (Chialina, et al, 2006;Jenkins, et al, 2002;Leach, et al, 1993;Southey, et al, 2005). Similar to studies in yeast expressing the equivalent mutant protein, yMSH2-P640L (Drotschmann, et al, 1999;Polaczek, et al, 1998), we observed a strong mutator phenotype in Msh2 P622L/P622L ESCs.…”
Section: Discussionsupporting
confidence: 85%
“…The Victorian Colorectal Cancer Family Study is a population-based, case-control family study of early-onset colorectal cancer, conducted from 1993 to 1997 on 131 cases of histologically verified primary adenocarcinomas of the colon or rectum registered on the Victorian Cancer Registry (1,18). The probands (all diagnosed between 18 and 44 years of age) consisted of 66 females and 65 males, with the mean age at diagnosis being 39.5 years (SD, 4.7 years).…”
Section: Methodsmentioning
confidence: 99%
“…In a population-based study of patients with young-onset CRC (age < 45 years), known to be negative for germ line mutations of hMLH1 and hMSH2, Jenkins et al (30) described a strong familial association in young-onset MSS CRC. Data presented by Chan et al (20) also support that there may be a significant hereditary component within the specific subgroup of young-onset MSS CINÀ CRC, with 50% of those with MSS CINÀ CRC having a family history of CRC.…”
Section: Proximal Colonmentioning
confidence: 99%